Determination of phosphorus pools, sorption capacity and supply potential of agricultural soils of Tigray, Northern Ethiopia - Reda, Gidena T.; Breure, Mirjam S.; Wall, David P.; Reda, Abbadi G.; Creamer, Rachel E. (Geoderma Regional, 2025)
Phosphorus (P) is a major limiting nutrient for food production in Ethiopian agricultural soils, primarily due to low P fertilizer application and strong P fixation caused by inherent soil properties. Understanding the supply potential and distribution of soil P pools is essential for optimising P fertilizer recommendations, particularly in Northern Ethiopian soils, where strong P fixation occurs due to highly weathered soil minerals, and associated soil properties, which affect P availability. The objectives of this study were to: (i) investigate the distribution of P across different soil P pools and (ii) examine the P sorption capacity and supply potential of agricultural soils in relation to P availability as controlled by Ca/P and Al/P ratios. Soil samples were collected from forty-three locations across three districts in northern Ethiopia: Endamekhoni (ED), Laelay-Maichew (LM) and Atsbi-Wenberta (AW). Availability and distribution of P across different soil P pools were assessed using Mehlich3 (M3) extraction and Hedley sequential extraction scheme, respectively. Soil total P was highly variable across sites, ranging between 348 and 3108 mg kg−1. The availability of P was plotted against ratios of Ca and Al over P to identify change points, indicative of P supply potential to crops. Results showed that the change points for P supply potential were different across the three districts, likely reflecting differences in soil parent materials. The Ca/P ratio change points that determine the availability of P in soils were 696:1, 1926:1 and 401:1, for the districts of ED, LM and AW, respectively. Similarly, the change points of Al/P ratio for the ED, LM and AW were 97:1, 284:1, and 30:1, respectively. The accessibility of P for plant uptake increased when the ratios of Ca/P and Al/P were below the change points and vice versa. In conclusion P fertilizer recommendations should consider the change points of Ca/P and Al/P ratios, as these ratios control the bioavailability of soil P and elucidate the P sorption capacity and supply potential of the Ethiopian agricultural soils.